The activity of some enzymes in Bon Chretien pears in relation to storage behaviour of the fruit - Ireland, J. P.(John Peter) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc. (Agric.)) -- University of Stellenbosch, 1964.